Strength and Durability Enhancement of Sustainable Flexible Pavements Using Waste Tires, PET Plastics, Polythene Sheets, and Bituminous Concrete - Alyamani, Mohannad (Engineering, Technology & Applied Science Research, 2026)
The present study investigates sustainable rehabilitation techniques for flexible pavements that utilize waste materials, including scrap tires, polyethylene sheets, and Polyethylene Terephthalate (PET) plastics. It evaluates various innovative techniques such as geo-tire confinement systems to enhance subgrade stability, polyethylene moisture barriers to reduce water penetration, and Thermo-Geo-Plastic (TGP) composites for pothole repair. Laboratory tests reveal that these methods significantly outperform traditional systems, showing increased Marshall stability and flow rates, which enhance load-bearing capacity and flexibility of the pavement. Modified mixtures show approximately 20% improvement in indirect tensile strength and reduced moisture susceptibility. Rutting tests demonstrate reduced permanent deformation and improved fatigue resistance, while permeability tests indicate that the polyethylene interlayers effectively reduce moisture infiltration by 21–60%. The TGP composite achieves compressive strengths of up to 18.81 MPa in field tests, indicating high durability. Microstructural analysis indicates stronger interactions between the aggregate and the binder, thereby improving mechanical properties. Field evaluations validate laboratory results, with noticeable improvements in pavement stability and reduced distress. These sustainable techniques not only improve pavement performance but also reduce waste materials for landfills, decrease embodied carbon emissions, and promote circular economy practices. The study demonstrates that integrating waste materials into pavement rehabilitation can enhance structural reliability, extend service life, and yield substantial environmental benefits.